IMPLEMENTASI TEORI THOMAS LICKONA TERHADAP PROBLEM KETIDAK JUJURAN - Indri Fitriyani (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2021)
Dishonesty is lying behavior and saying something not true,cheating or not following all applicable rules and being carried out by force and lies. The purpose of this research is to explore theoretically and deeply about the implementation of Thomas Lickona's theory in solving the problem of dishonesty. The method used in this research is literature research method. The results of this study indicate that the Thomas Lickona theory discusses character education. Honest behavior is part of character education and dishonesty can be overcome if individuals who experience it have a strong desire within themselves to continue the process of understanding the character in themselves. When applied to the problem of dishonesty, the theory offered by Thomas Lickona should involve three domains of character education in order to be effective, they are: moral knowing, moral feeling, and moral acting. Besides that, you must always include Allah based on Al Qur'an.